Antifungal Activity of Endophytic Bacillus K1 Against Botrytis cinerea - Li, Peiqian; Feng, Baozhen; Yao, Zhen; Wei, Bohui; Zhao, Yanfei; Shi, Shouguo (Frontiers in Microbiology, 2022)
Gray mold caused by Botrytis cinerea is detrimental to plants and fruits. Endophytes have been shown to modify plant disease severity in functional assays. We conducted this study to investigate the endophytic strain Bacillus K1 with excellently antagonistic B. cinerea from wild grape endosphere. We identified a wild grape endophytic strain K1 with high antifungal activity against B. cinerea both in vitro and vivo. Combining the phylogenetic results based on 16S rDNA and genome sequencing, K1 was assigned as Bacillus subtilis. The in vitro results displayed that K1 and its volatile substances could significantly inhibit mycelia growth of B. cinerea. Grape fruit inoculated with Bacillus K1 showed lower grey mold during treatment. The higher levels of defense-related enzymes including peroxidase, polyphenol oxidase, and phenylalanine ammonia lyase, were induced in grapes after inoculation. Scanning electron microscopy suggested that K1 inhibited mycelia growth via bacterial colonization and antibiosis in grapes. The gas chromatography-mass spectrometry analysis identified 33 volatiles, in which dibutyl phthalate was the major compound accounting for 74.28%. Dibutyl phthalate demonstrated a strong activity in suppressing mycelia growth of B. cinerea. Genome bioinformatic analysis revealed that K1 chromosome harbored many known biosynthesis gene clusters encoding subtilosin, bacillaene, bacillibactin, bacilysin, and fengycin. This study provides a potential biological agent to control diseases of postharvest grape fruit and improves our understanding of the possible biocontrol mechanisms of the Bacillus strain.